Study about Interpersonal Communication for Development - Ono, Gloria Nneka; Odionye, Chinwe Mirian (Research Developments in Arts and Social Studies Vol. 1, 2022)
This paper is aimed at extolling the overwhelming synergy between interpersonal communication and development while establishing that interpersonal communication is a must for meaningful and sustained development to take place. Specifically, basic concepts were defined, explained and appropriate examples given for better comprehension of the discourse. The paper goes further to discuss types of interpersonal communication, interpersonal communication in relationship, elements of interpersonal communication, and noise in communication as doing a great damage to the communication process. The paper adopted content analytical method whereby scholarly articles from books, journals and internet were analyzed. The authors advocate for channel mix whereby interpersonal communication can be mixed with the mass media and the social media for more effective sustainable development to be achieved. Finally, certain inferences and conclusions were made.